3D finite element analysis of braced excavation - Tan, Chong Beng (2018)
Most of the deep excavation project is modelled and analysed by using 2-Dimensional (2D) finite element analysis (FEA), with plane strain assumption. However, in the real construction project, due to the space constraint, the geometry of the excavation is usually non-symmetry. The focus of this study is to conduct 3-Dimensional (3D) finite element analysis (FEA) using the program, PLAXIS 3D and PLAXIS 2D, to study the 3D effect on different excavation geometry which includes different excavation length, different excavation depth, different size of square excavation and non-symmetry excavation. The results are compared with 2D FEA. Two case study are selected based on their geometry of the excavation, which are Siam Motor Machine Building (Chheng & Likitlersuang, 2017) and Building Construction in the Sinyi District, Taipei (Ou et al., 2010). To consider the geometry of the excavation and support systems, full 3D FEA were carried out on both case studies. The results obtained from the analysis are then compared with the field data reported in the case studies. The findings show that the geometry of the excavation did affect the performance of the excavation. 3D analysis better predicts the wall deflection, ground settlement and bending moment of the wall. Hence, when the 3D program is available, 3D FEA should be carried out instead of 2D FEA.